2005
DOI: 10.1021/bm0502157
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthetic Hydrophilic Polyals

Abstract: Nonbioadhesive, fully biodegradable soluble polymers would be very instrumental in advanced biomedical applications, such as gene and drug delivery and tissue engineering. However, rational development of such materials is hindered by the complexity of macromolecule interactions with biological milieu. The prevalence of carbohydrates in naturally occurring interface structures suggests an alternative, biomimetic approach. Interface carbohydrates, regardless of their biological function, have common nonsignalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
(37 reference statements)
1
20
0
Order By: Relevance
“…The chemistries employed have included polyacetals, ketals, and hydrazones. [41][42][43] In comparison to the 'one-shot' approaches described above, reversibly responsive polymers are especially applicable in devices or materials to combat conditions such as diabetes, where a specific or feedback-controlled release profile might be required. Polymers that respond in such a way to changes in local glucose concentrations by releasing insulin have been much studied [44][45][46][47] following initial reports by Ishihara and co-workers.…”
Section: Responsive Polymers In Drug Deliverymentioning
confidence: 99%
“…The chemistries employed have included polyacetals, ketals, and hydrazones. [41][42][43] In comparison to the 'one-shot' approaches described above, reversibly responsive polymers are especially applicable in devices or materials to combat conditions such as diabetes, where a specific or feedback-controlled release profile might be required. Polymers that respond in such a way to changes in local glucose concentrations by releasing insulin have been much studied [44][45][46][47] following initial reports by Ishihara and co-workers.…”
Section: Responsive Polymers In Drug Deliverymentioning
confidence: 99%
“…All previously tested PHF-containing preparations with MW exceeding 70 kDa exhibited long circulation in vivo, with no significant uptake in RES. The blood half-life of unmodified 500 kDa PHF was found to be over 24 h. 10,28 At a 1:1 polymer/protein ratio, two conjugation techniques gave the highest coupling yields (95-98% by protein): the one-step method utilizing aminooxy-NHS coupling reagent VIII and polymer succinylation followed by EDC-mediated acylation. Conjugate formation was accompanied with a 1.5 to 2.0-fold increase in the number-average molecular weight (M n ).…”
Section: Discussionmentioning
confidence: 99%
“…The structures of all obtained polymers, as examined by 13 C and 1 H NMR, were consistent with the expected acyclic polyacetal structure. 10,28 PHF-glycol PHF-glycol was prepared by controlled dextran cleavage that was stopped at stage II, with subsequent reduction of intermediates (IIa, IIb). The starting glucopyranoside/periodate molar ratio was 1:1.90.…”
Section: Poly-1-hydroxymethylethylene Hydroxymethyl-formal IV (Phf)mentioning
confidence: 99%
“…While polyesters and polyanhydrides are all widely characterized and under development for biomedical applications, they are not biologically inert and may non-specifically react with the surrounding in vivo environment (53). Polyesters and polyanhydrides, as well as other similarly structured polymers, degrade via hydrolysis and give rise to products with carboxylic acid terminal groups.…”
Section: Polyanhydridesmentioning
confidence: 99%
“…Previous studies have also shown that accumulation and increased concentration of acidic degradation products can induce tissue toxicity (28,29,56). To address these issues, a new class of synthetic, polymeric biomaterials based upon degradable units such as acetals, cyclic acetals, and ketals have been developed (22,24,53).…”
Section: Polyanhydridesmentioning
confidence: 99%